IDENTIFIKASI SERANGGA HAMA PADA TANAMAN PADI DI PROVINSI BENGKULU - Febrianto, Sudi; Sunarti; Sridanti, Irma Lisa (University of Prof. Dr. Hazairin, SH, 2024)
Insect pests are a serious threat to rice production because they can cause various disease symptoms that cause significant damage to rice plants, resulting in decreased production. This study focused on identifying insect pests in rice plants in Bengkulu Province. This study aims to identify insect pest species in rice plants in various research locations covering the highlands and lowlands in Bengkulu Province. This study was conducted in July-August 2024. Sampling was conducted using insect nets, and insect pest identification was carried out. The analysis method used is a qualitative descriptive method. This study produced several main insect pest species, namely the seedling fly (Atherigona oryzae), rice orange leafhoppers (Cicadulina bipunctata), rice leaf folder (Cnaphalocrocis medinalis), rice bugs (Leptocorisa oratoriuis), green paddy leafhoppers (Nephotettix virescens), rice stem gall midge (Orseolia oryzae), green grasshoppers (Oxya japonica), green grasshoppers (Oxya serville), zigzag leafhopper (Recilia dorsalis), Ebarrius cognatus, rice black bug (Scotinopara coartata), and yellow stem borer (Scripophaga interculas) in various research locations. The level of insect attack varied in each location, with some locations showing higher levels of attack than others.